From power asymmetry to collective action: Brazilian developers in the digital games ecosystem - Charles Kirschbaum; Luiz Ojima Sakuda (Innovation & Management Review)
Purpose – The purpose of the article is to explore the perceptions of Brazilian game developers about the power relations between them and the sponsors of digital game platforms. It also aims to identify forms of collective action that developers can use to counteract the asymmetry of power. Design/methodology/approach – The research employed an abductive approach, seeking empirical evidence that would challenge consolidated theory. To achieve this, semi-structured interviews were conducted with 25 Brazilian developers. The data were analyzed qualitatively using NVivo software. The aim was to resolve theoretical ambiguities identified in the literature review and to explore unexpected findings. Findings – The study explores Brazilian game developers' perceptions through interviews, revealing their experiences within the industry’s concentrated structure and their use of collective action to navigate power dynamics. Research limitations/implications – The study's focus on Brazil limits the generalizability of its findings to the broader game development industry. Practical implications – The study suggests Brazilian game devs can leverage collective action to counteract power imbalance with platforms, collaborate through events and projects and facilitate internationalization of their games. Social implications – The study suggests collective action could empower developers to challenge platform dominance and foster a stronger community among Brazilian game developers. Originality/value – The article’s value lies in examining Brazilian devs' experiences within their specific industry context and highlighting collective action as a potential strategy for developers.